Proceedings of the 2019 ACM Conference on Economics and Computation 2019
DOI: 10.1145/3328526.3329635
|View full text |Cite
|
Sign up to set email alerts
|

The Perils of Exploration under Competition

Abstract: We empirically study the interplay between exploration and competition. Systems that learn from interactions with users often engage in exploration: making potentially suboptimal decisions in order to acquire new information for future decisions. However, when multiple systems are competing for the same market of users, exploration may hurt a system's reputation in the near term, with adverse competitive effects. In particular, a system may enter a "death spiral", when the short-term reputation cost decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…An algorithm may even enter a "death spiral", when the short-term reputation cost decreases the number of users for the algorithm to learn from, which degrades the system's performance relative to competition and further decreases the market share. Mansour et al (2018); Aridor et al (2019) investigate whether competition incentivizes the adoption of better bandit algorithms, and how it depends on the intensity of the competition. They relate these questions to the relationship between competition and innovation, a well-studied topic in economics (Schumpeter, 1942;Aghion et al, 2005).…”
Section: Agents Choose Between Bandit Algorithmsmentioning
confidence: 99%
“…An algorithm may even enter a "death spiral", when the short-term reputation cost decreases the number of users for the algorithm to learn from, which degrades the system's performance relative to competition and further decreases the market share. Mansour et al (2018); Aridor et al (2019) investigate whether competition incentivizes the adoption of better bandit algorithms, and how it depends on the intensity of the competition. They relate these questions to the relationship between competition and innovation, a well-studied topic in economics (Schumpeter, 1942;Aghion et al, 2005).…”
Section: Agents Choose Between Bandit Algorithmsmentioning
confidence: 99%
“…It could well occur that the initial samples are less effective because, e.g., initially the advertised product is not yet well established which leads customers to prefer alternative options. In fact, recent work has suggested that, under competition, learning algorithms generally suffer from such an effect due to the exploration they need to perform in the beginning; see [MSW18] and [ALSW19] for a relevant discussion.…”
Section: Cold Start Attackmentioning
confidence: 99%
“…Aridor, Liu, Slivkins, and Wu [ALSW19] empirically study the interplay between exploration and competition in a model where multiple firms are competing for the same market of users and each firm commits to a multi-armed bandit algorithm. The objective of each firm is to maximize its market share and the question is when firms are incentivized to adopt better algorithms.…”
Section: Bolton and Harrismentioning
confidence: 99%